STRUKTUR JALAN LAYANG PROVINSI DKI JAKARTA: SEBUAH KAJIAN EVALUASI KUALITAS VISUAL - Ray March Syahadat; Priambudi Trie Putra; Tandri Patih; Dimas Muhammad Thoifur; Fitria Nurhasanah; Ismail Saleh (Jurnal Infrastruktur, 2019)
Rapid urban development demands a lot of infrastructure development. The development aims to support the activities of urban communities. Many research has been done on the structure, but the assessment of the visual quality of these structures is still very rarely done, especially in Indonesia. Flyovers are one of the structures that are often present in cities to solve congestion problems. Jakarta as the capital city, has many of these structures. Unfortunately, unwittingly adding structures can affect the visual quality of the surrounding environment. There are many ways to beautify these structures such as by adding plants, giving ornaments in the form of reliefs, to painting with mural art. The purpose of this article is to evaluate the visual quality of flyover structures. The methods used in this article include scenic beauty estimation (SBE), semantic differential (SD), factor analysis, multidimensional scaling, and Kendall’s W. The results obtained are different levels of visual quality of flyover structures based on the appearance of complementary ornaments. Based on SBE analysis, the structure with reliefs that were not colored showed poor visual quality with an SBE value of -46,483. High visual quality based on SBE analysis, namely the structure with the softscape element in the form of landscape plants (89,777). The impression caused by the structure with softscape elements in the form of landscape plants is considered shadier and attractive.